CONTROL OF ANTIBIOTICS RESIDUAL AMOUNTS CONTENT IN PRODUCTS OF ANIMAL ORIGIN - Klyap, N. I.; Krachkovska, O. O.; Maslyuk, A. V.; Mostipan, K. S.; Kyivska, G. V. (Scientific Progress & Innovations, 2020)
Antibiotic resistance of the main causative agents of infectious diseases is one of the most important problems of modern human and veterinary medicine. One of the reasons for total spreading of this threaten-ing phenomenon has been excessive and irrational applying of antibiotics in livestock farming. Consuming food products of animal origin contaminated with residual amounts of these preparations can result in dete-riorating general health condition, allergic reactions and developing antibiotic resistance of major causative agents of infectious diseases. This problem necessitates controlling products of animal origin for the content of antibiotics residual amounts. The purpose of our research was to analyze and summarize the results of studies on exceeding the permissible levels of antibiotics residual amounts in products of animal origin, which were tested in State Scientific-Research Institute at the Laboratory of Diagnostics and Veterinary-Sanitary Expertise during 2017–2019. The tests were conducted by enzyme-linked immune-sorbent assay (ELISA). The results analysis of the study conducted during 2017–2019 shows that residual amounts of anti-biotics were found in livestock products manufactured in different regions of Ukraine. In some samples of products of animal origin, the concentrations of antibiotics residual amounts were found, which exceeded CCβ value (0.2–3.9 % of the total number of tested samples). In 2019, exceeding the value of CCβ was re-vealed concerning chloramphenicol in pork samples (0.2 % of the total number of samples tested for this indicator), nitrofuran metabolites in rabbit meat samples (0.5 % of the total number of samples tested for these indicators). In addition, exceeding the value of CCβ in egg samples was found as to the content of amoxicillin residual amounts – 0.5 %, enrofloxacin – 0.4 %, ciprofloxacin – 0.4 %, norfloxacin – 0.4 %, flumequine – 0.4 % and tylosin – 1.3 % of the total number of samples tested for these indicators. The pre-sented results of scientific research highlight the necessity of controlling the content of residual amounts of the above mentioned preparations in food products of animal origin.